Partial CD25 Antagonism Enables Dominance of Antigen-Inducible CD25high FOXP3+ Regulatory T Cells As a Basis for a Regulatory T Cell-Based Adoptive Immunotherapy - Wilkinson, Daniel S.; Ghosh, Debjani; Nickle, Rebecca A.; Moorman, Cody D.; Mannie, Mark D. (Frontiers in Immunology, 2017)
FOXP3+ regulatory T cells (Tregs) represent a promising platform for effective adoptive immunotherapy of chronic inflammatory disease, including autoimmune diseases such as Multiple Sclerosis. Successful Treg immunotherapy however requires new technologies to enable long-term expansion of stable, antigen-specific FOXP3+ Tregs in cell culture. Antigen-specific activation of naïve T cells in the presence of TGF-β elicits the initial differentiation of the FOXP3+ lineage, but these Treg lines lack phenotypic stability and rapidly transition to a conventional T cell (Tcon) phenotype during in vitro propagation. Because Tregs and Tcons differentially express CD25, we hypothesized that anti-CD25 monoclonal antibodies (mAbs) would only partially block IL-2 signaling in CD25high FOXP3+ Tregs while completely blocking IL-2 responses of CD25low-intermediate Tcons to enable preferential outgrowth of Tregs during in vitro propagation. Indeed, murine TGF-β-induced MOG-specific Treg lines from 2D2 transgenic mice that were maintained in IL-2 with the anti-CD25 PC61 mAb rapidly acquired and indefinitely maintained a FOXP3high phenotype during long-term in vitro propagation (>90% FOXP3+ Tregs) whereas parallel cultures lacking PC61 rapidly lost FOXP3. These results pertained to TGF-β-inducible ‘iTregs’ because Tregs from 2D2-FIG Rag1-/- mice, which lack thymic or natural Tregs, were stabilized by continuous culture in IL-2 and PC61. MOG-specific and polyclonal Tregs up-regulated the Treg-associated markers Neuropilin-1 (NRP1) and Helios (IKZF2). Just as PC61 stabilized FOXP3+ Tregs during expansion in IL-2, TGF-β fully stabilized FOXP3+ Tregs during cellular activation in the presence of dendritic cells and antigen/ mitogen. Adoptive transfer of blastogenic CD25high FOXP3+ Tregs from MOG35-55-specific 2D2 TCR transgenic mice suppressed experimental autoimmune encephalomyelitis (EAE) in pretreatment and therapeutic protocols. In conclusion, low IL-2 concentrations coupled with high PC61 concentrations constrained IL-2 signaling to a low-intensity range that enabled dominant stable outgrowth of suppressive CD25high FOXP3+ Tregs. The ability to indefinitely expand stable Treg lines will provide insight into FOXP3+ Treg physiology and will be foundational for Treg-based immunotherapy.